1997
DOI: 10.1111/j.1346-8138.1997.tb02748.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Nitric Oxide Synthase in Normal Human Skin: Expression of Endothelial‐type and Inducible‐type Nitric Oxide Synthase in Keratinocytes

Abstract: Nitric oxide (NO) is a critical mediator of various biological functions. NO is generated from L-arginine by nitric oxide synthase (NOS), which has three isoforms; endothelial-type NOS (eNOS) and brain-type NOS (bNOS) are constitutive enzymes, and inducible-type NOS (iNOS) is expressed after stimulation. We investigated the expression of NOS in normal human skin by an immunohistochemical technique and western blotting analysis. In human skin, epidermal keratinocytes and the outer root sheath were labeled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 64 publications
8
56
0
Order By: Relevance
“…It previously has been shown by immunohistochemistry that both human skin and nasal mucosal MCs also are positive for nNOS. 17,25 Thus, our nNOS results with ex vivo HSMCs are compatible with those in vivo studies, and there are significant differences in NOS expression in human MC populations contributing further to MC heterogeneity.With the lack of constitutive iNOS expression, human MCs appear to rely on constitutive (cNOS) in their quiescent state. This pattern is reiterated in other human immune cells, with neutrophils and eosinophils also being identified as cNOS expressors, employing eNOS and nNOS isoforms.…”
supporting
confidence: 77%
“…It previously has been shown by immunohistochemistry that both human skin and nasal mucosal MCs also are positive for nNOS. 17,25 Thus, our nNOS results with ex vivo HSMCs are compatible with those in vivo studies, and there are significant differences in NOS expression in human MC populations contributing further to MC heterogeneity.With the lack of constitutive iNOS expression, human MCs appear to rely on constitutive (cNOS) in their quiescent state. This pattern is reiterated in other human immune cells, with neutrophils and eosinophils also being identified as cNOS expressors, employing eNOS and nNOS isoforms.…”
supporting
confidence: 77%
“…We also detected eNOS gene transcriptional expression through RT-PCR analysis, suggesting that eNOS is synthesized by umbilical cord cells. In agreement with our data, eNOS expression, typical of endothelia, has also been reported in other types of tissues and cells, such as many epithelium, fibroblasts, cardiomyocytes, osteocytes and glial cells [32][33][34][35].…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 92%
“…The present observation is basically in line with earlier findings of TNF-mediated enhanced production of NO in cultured peritoneal and intestinal mast cells (Bissonnette et al, 1991), however, NO production was at that time not attributable to a certain NOS isoform. There is inconsistent information about NOS isoenzyme expression in mast cells of different organs: positive bNOS immunoreactivity has been reported for human skin mast cells (Shimizu et al, 1997), whereas both mouse myometrial (Huang et al, 1995) and connective tissue mast cells (Bidri et al, 1997) showed iNOS expression after hormonal or antigen stimulation. Further studies should address the issue of whether the up-regulation of eNOS in response to LPS in mast cells as opposed to other cell types is a lung-specific finding or is representative for mast cells of other organ origin.…”
Section: Ermert Et Almentioning
confidence: 99%